(untitled) (Docentes 2.0 Journal, 2023)
The teaching of history plays a fundamental role in the citizenship education of students; however, the predominance of traditional history education hinders the achievement of this formative purpose. In this context, artificial intelligence (AI) emerges as an innovative tool that can enrich students’ historical learning. This essay was conducted under the inductive method, the humanistic paradigm, with a qualitative approach, interpretative type, and topical narrative design. The objective was to analyze the challenges and opportunities of artificial intelligence (AI) in teaching history, examine the use of this technology, and describe the key applications in this subject. In this regard, technical challenges were identified, such as the accuracy of algorithms and the availability of digitized historical documents, as well as ethical considerations related to student privacy, limited human interaction in AI systems, and the adoption of diverse historical interpretations in the narration of past events; despite this, it is argued that AI can improve students’ historical understanding and transform their educational experience. In conclusion, it is recommended to carry out additional research and reflections to delve into the subject and insist on addressing technical limitations and maintaining a balanced pedagogical approach between AI and human interaction in history teaching to train critical and responsible citizens.